THE IMPACT OF AN INITIAL FOOD AND A DIFFERENT FEED COMBINATIONS ON THE GROWTH AND SURVIVAL OF SILVER BARB LARVAE (Barbonymus gonionotus) - Sori Pada Pulungan; Hamdan Alawi; Nuraini Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThe research was carried out for 40 days from 18 April to 28 May2019, in the fish hatchery and BreedingLaboratoryDepartment of Aquaculture, Faculty of Fisheries and Marine. University of Riau. The purpose of this researchwas to determine the effect of initial feeding and different feed combinations on the growth and survival of silver barb larvae (Barbonymusgonionotus). The larvae was reased for 40 days, in 16 -Lplastic jar, with 2Larvae/L.The larvae were stockedat 20 larvae/jar. The method used in this research was the experimental method. The design used was a Completely Randomized Design (CRD) one factor with six treatments and three replications. The treatments used were P1 (Chlorella sp.), P2 (Artemia nauplii), P3 (Water Fleas), P4 (Chlorella sp. + Artemia nauplii), P5 (Chlorella sp. +Water Fleas), P6 (Chlorellasp. + Artemia nauplii + Water Fleas). The results showed that the combination of feeding was significantlyeffectto the growth and survival rate of barb larvae. The best results obtained in the treatment of P6 (Chlorella sp. + Artemia nauplii+ Water Fleas) produced absolute weight growth of 1.02 g, absolute length growth of 4.29 cm, specific growth rate of 14.75% and survival rate of 95%. Water quality during the study was temperature ranging from 25.3-27.80C, pH 5.1-6.5 and DO of 4.1-5.2 ppm. Keywords : Combinations, Natural Feeds, Silver Barb (Barbonymus gonionotus), Chlorella sp., Artemia nauplii., Water Fleas.